Water quality assessment using Sentinel-2 imagery with estimates of chlorophyll a, Secchi disk depth, and Cyanobacteria cell number: the Cantareira System reservoirs (São Paulo, Brazil) - Pompêo, Marcelo; Moschini-Carlos, Viviane [UNESP]; Bitencourt, Marisa Dantas; Sòria-Perpinyà, Xavier; Vicente, Eduardo; Delegido, Jesus (Springer Nature, 2021)
Satellite images were used to assess surface water quality based on the concentration of chlorophyll a (chla), light penetration measured by the Secchi disk method (SD), and the Cyanobacteria cells number per mL (cyano). For this case study, six reservoirs interconnected were evaluated, comprising the Cantareira System (CS) in São Paulo State (Brazil). The work employed Sentinel-2 images from 2015 to 2018, SNAP image processing software, and the native products conc_chl and kd_z90max, treated using Case 2 Regional Coast Color (C2RCC) atmospheric correction. The database was obtained from CETESB, the agency legally responsible for operation of the Inland Water Quality Monitoring Network in São Paulo State. The results demonstrated robustness in the estimates of chla (RMSE = 3.73; NRMSE% = 19%) and SD (RMSE = 2,26; NRMSE% = 14%). Due to the strong relationship between cyano and chla (r2 = 0.84, p < 0.01, n = 90), both obtained from field measurements, there was also robustness in cyano estimates based on the estimates of chla from the satellite images. The data revealed a clear pattern, with the upstream reservoirs being more eutrophic, compared to those downstream. There were evident concerns, about water quality, particularly due to the high numbers of Cyanobacteria cells, especially in the upstream reservoirs.
Keywords: C2RCC; Chlorophyll; Cyanobacteria; Remote sensing; Secchi disk; Sentinel-2; Tropical reservoirs